2012
DOI: 10.1002/adsc.201200532
|View full text |Cite
|
Sign up to set email alerts
|

Acceptorless and Base‐Free Dehydrogenation of Alcohols and Amines using Ruthenium‐Hydride Complexes

Abstract: An efficient, operatively simple, acceptorless, and base-free dehydrogenation of secondary alcohols and nitrogen-containing heterocyclic compounds was achieved by using readily available ruthenium hydride complexes as precatalysts. The complex RuH 2 (CO)A C H T U N G T R E N N U N G (PPh 3 ) 3 (1) and Shvos complex (2) showed excellent activities for the dehydrogenation of secondary alcohols and nitrogen containing heterocycles. In addition to complexes 1 and 2, the complex RuH 2 A C H T U N G T R E N N U N G … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
63
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(64 citation statements)
references
References 96 publications
1
63
0
Order By: Relevance
“…[18] Our own computational results have corroborated this scenario, finding such paths competitive, if not preferred for the higher alcohols. [6] Because both tris-and bis(phosphine) intermediates are plausible intermediates, [6][7]19] we now turn to a mechanistic alternative for decarbonylation involving phosphine dissociation. To make this path comparable to the one just discussed, we start from isomer 13H on the dehydrogenation pathway C(neutral), see Figure 3a.…”
Section: Reaction Mechanisms Involving Methanol As Substratementioning
confidence: 99%
See 1 more Smart Citation
“…[18] Our own computational results have corroborated this scenario, finding such paths competitive, if not preferred for the higher alcohols. [6] Because both tris-and bis(phosphine) intermediates are plausible intermediates, [6][7]19] we now turn to a mechanistic alternative for decarbonylation involving phosphine dissociation. To make this path comparable to the one just discussed, we start from isomer 13H on the dehydrogenation pathway C(neutral), see Figure 3a.…”
Section: Reaction Mechanisms Involving Methanol As Substratementioning
confidence: 99%
“…Not only can the produced aldehydes undergo aldol and Tischenko reactions under the reaction conditions, they can also react with the Ru catalyst in a decarbonylation reaction generating carbonyl complexes such as [RuH 2 (CO)(PPh 3 ) 3 ] (22, see Scheme 1). 22 is also active as a dehydrogenation catalyst, [5,7] adding to the complexity of the system. [8] As 22 can be readily prepared under similar conditions (in methanol or ethanol, in presence of base and under a flux of hydrogen gas), [9] there should be a significant driving force for its formation under catalytic conditions, at the expense of dehydrogenation.…”
Section: Introductionmentioning
confidence: 99%
“…Homogeneous catalysts for the acceptorless dehydrogenation of primary and secondary alcohols for the most part contain precious metals, such as Ru (19), Rh (20), and Ir (21). By comparison,…”
mentioning
confidence: 99%
“…Although the transfer dehydrogenation step with 1.5 equivalents of quinone efficiently oxidized N ‐phenyl‐1‐phenylethylamine to the corresponding imine with a yield of 97 % (turnover frequency (TOF) of 24 h −1 ), it must be noted that the coupled system (which includes reoxidation of only 20 mol % of quinone) was significantly less active, achieving a TOF of only 7 h −1 (88 % selectivity). Thereafter, Hong and Muthaiah reported that ruthenium hydride complexes, such as RuH 2 (CO)(PPh 3 ) 3 and Shvo's complex, are also effective catalysts for the dehydrogenation of N‐containing heterocycles, under “acceptorless” and base‐free conditions . Later, a very interesting result was published by Szymczak's group where they demonstrated an amide‐derived NNN‐Ru II hydride complex catalyzes the oxidant‐free, acceptorless, and chemoselective dehydrogenation of primary and secondary amines to the corresponding nitriles and imines with the liberation of dihydrogen .…”
Section: Nitriles and Iminesmentioning
confidence: 99%